Communist Daze : The Many Misadventures of a Soviet Doctor - Tsesis, Vladimir (Book collections on Project MUSE., 2017)
This darkly comic memoir "reveal[s] much about the poverty, drunkenness, political corruption, anti-Semitism, and fundamental absurdity of rural life in the Soviet 1960s" (Deborah A. Field author of Private Life and Communist Morality in Khrushchev's Russia). Welcome to Gradieshti, a Soviet village awash in gray buildings and ramshackle fences, home to a large, collective farm and to the most oddball and endearing cast of characters possible. For three years in the 1960s, Vladimir Tsesis-inestimable Soviet doctor and irrepressible jester-was stationed in a village where racing tractor drivers tossed vodka bottles to each other for sport; where farmers and townspeople secretly mocked and tried to endure the Communist way of life; where milk for children, running water, and adequate electricity were rare; where the world's smallest, motley parade became the country's longest; and where one compulsively amorous Communist Party leader met a memorable, chilling fate. From a frantic pursuit of calcium-deprived, lunatic Socialist chickens to a father begging on his knees to Soviet officials to obtain antibiotic for his dying child, Vladimir's tales of Gradieshti are unforgettable. Sometimes hysterical, often moving, always a remarkable and highly entertaining insider's look at rural life under the old Soviet regime, they are a sobering expose of the terrible inadequacies of its much-lauded socialist medical system. "To understand the confusing reality of Russia today, it helps to recall the 'bad old days' of the late, unlamented Soviet Union. This warm, touching and occasionally hilarious book can assist those recollections."--Michael Medved, nationally syndicated radio show host.